Rural Farm and Non-farm Linkages in a Predominantly Manufacturing Region: The Case of Semarang Regency, Indonesia - Puji Hardati; Rijanta Rijanta; Su Ritohardoyo (Indonesian Journal of Geography, 2020)
This paper aimed to explore the correlation between the agricultural and non-agricultural sectors in the rural area affected by the manufacturing industry agglomeration of Semarang. Data on agricultural commodities, non-agricultural labor, and economic service facilities were reduced using factor analysis to form the typology of agricultural commodity areas and typology of rural diversification respectively. The two groups of score factors were correlated to predict the magnitude, direction, and significance of the inter-sectoral linkages. Data interpretation was made with the help of agricultural commodity flow data from the selected market. The study confirms the weak linkages between large-scale manufacturing industries and the agricultural economy in the hinterland. The study reflects weak linkages between the agricultural sector and rural diversification, as indicated by the weak correlation between factor scores. A rather strong linkage is shown by dryland agricultural areas associated with inland fisheries and rural diversification associated with tourism.